Mitigating the stress of transition: An exploration of the effects and effectiveness of a preparatory course for junior obstetric trainees transitioning to senior training roles. (September 2022) - Monteith, Cathy; Ní Bhuinneáin, Méabh; Geary, Michael P.
Abstract: Background: Attrition amongst obstetrics trainees is high worldwide and attributed to sources of stress and burnout. The role of formal education and simulation as a means to prepare trainees for stressful periods such as transition into senior roles is underexplored. Objective: This study set out to explore whether the creation of a dedicated educational intervention might positively influence burnout and self-estimated preparedness for practice among obstetric trainees transitioning into more senior roles. Study design: A six-week preparatory training programme for year 2 trainees was created specifically for this study. The intervention used the flipped classroom design incorporating online learning that prepared participants for six simulation-based workshops. Participants were randomised by training cluster into an intervention group (n = 4) who participated in the educational intervention and a control group (n = 7) who received standard online and workplace training. The effects on trainee well-being was assessed using the Maslach burnout inventory (MBI) and a self-report questionnaire estimating preparedness for practice. Technical and non-technical skills were assessed using standardised OSAT and NOTSS assessment tools. The primary outcomes were MBI and preparedness for practice scores. Secondary outcomes included OSAT and NOTSS scores. Group comparisons were made using by t -test or Pearson Chi 2 analysis where appropriate. Results: The study indicated a positive, non-significant trend in pre-post burnout scores in the intervention group. The following improving trends were noted in all subscales: emotional exhaustion 21.5 ± 2.6 (pre-intervention 23 ± 6.2); depersonalisation 9.8 ± 4.0 (pre-intervention 12.3 ± 2.8); personal accomplishment 35.5 ± 6.51 (pre-intervention 33 ± 5.5). The educational intervention engendered an increase in self estimated preparedness for practice amongst the intervention group (p = 0.006). From a training perspective, increased preparedness was noted for the following practical skills: forceps delivery (p = 0.0001), rotational forceps delivery (p = 0.02), delivery of twins vaginally (p = 0.0007) and performing a pudendal block (p = 0.001). Conclusion: This is one of the first studies to investigate whether the provision of a targeted training module can improve burnout scores and preparedness for practice amongst obstetrics trainees at an important time of transition. The positive but largely non-significant findings of this study should be examined in larger longitudinal and adequately powered studies.